Evaluasi Kebijakan Konservasi Kota Kecil Lasem, Kabupaten Rembang - Novita Tri Anggraenie; Jawoto Sih Setyono (Teknik PWK (Perencanaan Wilayah Kota), 2020)
Urban conservation in development planning is  a form of maintaining the city's heritage. It will be difficult and important to discuss about urban conservation, especially in small cities that have historical heritage. Urban conservation can’t be separated from a regulation, because it is the main thing of conservation planning. Existing policies must be able to accommodate mechanisms to balance conservation sustainability in the short and long term. In addition, urban conservation policies should be a tool that can control cultural heritage. This is the basis for reviewing policy documents relating to urban conservation as one of the terms of reference for development and activities in Lasem. The purpose of this study is to evaluate conservation policies in Lasem, Rembang Regency. The analytical method used is the Delphic Hierarchy Process (DHP) and descriptive statistical analysis. The results of the evaluation can be seen that the most important conservation policies are at the National level. With the existence of this research, it is expected to be considered in the formulation of conservation policies in Lasem, Rembang Regency.